Determinants of Financial Inclusion in the OIC and OECD Countries: Are They Different? - Tengku Roziana; Mohamed Eskandar Shah; Mohamed Ariff; Mohammed Umar (Journal of Islamic Monetary Economics and Finance, 2026)
Financial inclusion is a pivotal policy tool to integrate the underprivilege segments of society into the formal financial system. This issue is particularly important within predominantly Muslim nations, where poverty and inequality remain persistent challenges, and a substantial portion of the populace remains excluded from financial services. This seems to be paradoxical, especially given the substantial expansion of Islamic finance over the preceding decade. Therefore, this research aims to investigate the factors that determine financial inclusion within Organisation of Islamic Cooperation (OIC) member states. To put our findings into perspective, we compare our analysis with Organisation of Economic Co-operation and Development (OECD) countries. We use Least Square Dummy Variable (LSDV) estimator across 35 OIC and OECD countries from the period of 2005 to 2021. Our study finds that in OIC countries income per capita, tertiary education attainment, institutional quality, internet accessibility, population and age dependency matter for financial inclusion. Unlike OECD, OIC countries have to make substantial investment on digital infrastructures, youth and women empowerment, and boosting income level. Lessons are also drawn for Islamic banking in these countries.